2011
DOI: 10.12681/mms.48
|View full text |Cite
|
Sign up to set email alerts
|

New Mediterranean Biodiversity Records (December 2011)

Abstract: no abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…Since then, several reports validate its presence in the eastern Mediterranean basin, but until recently its known range of establishment was mostly restricted to the Levantine Sea, and more specifically to the coasts of Israel, Lebanon, Cyprus, and south-western Turkey (Crocetta et al, 2013 and references therein). However, according to a previous report in Eleftheriou et al (2011) and additional observations presented herein, the actual distribution range of F. rubrolineata seems to have expanded into the Aegean Sea (Greece). Several sightings of this nudibranch have been recorded since 2009 in different parts of the Aegean Sea (Fig.…”
Section: New Records Of the Non-indigenous Nudibranchsupporting
confidence: 75%
“…Since then, several reports validate its presence in the eastern Mediterranean basin, but until recently its known range of establishment was mostly restricted to the Levantine Sea, and more specifically to the coasts of Israel, Lebanon, Cyprus, and south-western Turkey (Crocetta et al, 2013 and references therein). However, according to a previous report in Eleftheriou et al (2011) and additional observations presented herein, the actual distribution range of F. rubrolineata seems to have expanded into the Aegean Sea (Greece). Several sightings of this nudibranch have been recorded since 2009 in different parts of the Aegean Sea (Fig.…”
Section: New Records Of the Non-indigenous Nudibranchsupporting
confidence: 75%
“…The first record in Hellenic waters dates back to 1947-1948(Serbetis, 1959, but Nehring (2011) suggested that the species was present as early as 1935 in the Gulf of Thessaloniki. Recent records in the Adriatic-Ionian Sea refer to Croatia (Onofri et al, 2008;Dulčić et al, 2011), Italy (Florio et al, 2008), Albania (Beqiraj and Kashta, 2010) and Greece (Eleftheriou et al, 2011). The last record was based on a female specimen collected close to the mouth of the River Pamisos in SW Greece and therefore, documentation on the presence of the species is lacking for a large part of the Eastern Ionian Sea, ranging from northern Albania to southern Greece.…”
Section: Documentation On the Establishment Ofmentioning
confidence: 99%
“…This caprellid, identified later as Caprella scaura (Templeton 1836) by Sandro Ruffo (Krapp et al 2006), represented the first and only introduced caprellid reported in the Mediterranean Sea. During the last decade, this Indopacific species has spread very fast across the Mediterranean Sea and has expanded its non-native range to the East Atlantic coast (Sconfietti et al 2005;Krapp et al 2006;Galil 2008;Martínez and Adarraga 2008;Ben Souissi et al 2010;Bakir and Katagan 2011;Guerra-García et al 2011a;Eleftheriou et al 2011). In September 2010, an established population of another alien caprellid, the tropical species Paracaprella pusilla Mayer 1890, was found for the first time in European waters, in the fouling community of a marina on the southwest Atlantic coast of Spain (Ros and GuerraGarcía 2012).…”
Section: Introductionmentioning
confidence: 99%